The impact of different drying methods on antioxidant activity, polyphenols, vitamin C and rehydration characteristics of Kiwifruit. (August 2022) - Bhat, Tashooq Ahmad; Hussain, Syed Zameer; Wani, Sajad Mohd; Rather, Mohd Ashraf; Reshi, Monica; Naseer, Bazila; Qadri, Tahiya; Khalil, Aroosa
Abstract: Kiwifruits were dried with convection drying, microwave drying and hybrid drying methods (hot air + microwave). Effect of different drying treatments-convection drying (CD), microwave drying (MD) and hybrid drying (HD) on physicochemical, nutritional and anti-oxidant properties of kiwifruits were investigated. The hybrid drying technique significantly reduced drying time and increased drying rate as compared to other drying methods. Hybrid dried kiwifruit slices showed the best texture attributes (low hardness, low shrinkage), better color (L*, a*, b*) and were rated best in sensory evaluation. High retention of bio-active compounds and reduced browning was also found in HD kiwifruit slices. Correlation analysis results showed significant positive correlation of phenols with antioxidant capacity. Drying methods significantly (p < 0.05) reduced protein and fat content of dried kiwi slices. However, a predominant decrease in protein and fat content was recorded in individual drying methods (Convection drying and Microwave drying). Hence, HD could be a more promising technique for development of dried kiwifruit slices. Graphical abstract: Image 1